The importance of the personnel security mechanism of the enterprise - Garmash, Sergii (My University, 2023)
It is difficult to underestimate the importance of human resources in the survival of any enterprise in modern conditions. First of all, it concerns the mechanism of ensuring personnel security of the enterprise and the key role that this mechanism plays in the system of economic security of the enterprise as a whole.
Keywords: total corruption; nepotism; personnel security mechanism; modern industrial enterprises; competence of human resources